2014
DOI: 10.1111/cid.12218
|View full text |Cite
|
Sign up to set email alerts
|

On the Early Mechanisms of Bone Formation after Maxillary Sinus Membrane Elevation: An Experimental Histological and Immunohistochemical Study

Abstract: Bone formation after sinus membrane elevation with or without additional bone grafts starts at the sinus floor and sprouts into the elevated space along the implant surface. The sinus membrane does not seem to present osteoinductive potential in sinus membrane elevation procedures in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
46
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 24 publications
4
46
0
Order By: Relevance
“…Elevation of the Schneiderian membrane and tenting effect of the simultaneously inserted dental implants seem to be sufficient for endo‐sinus bone gain. This is in line with histological findings from sites treated with membrane elevation without grafting that demonstrated bone tissue formation from the coagulum under the lifted membrane . Previous radiographic examinations identified OSFE procedure without grafting material as predictable treatment approach for posterior maxilla with limited residual bone height.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Elevation of the Schneiderian membrane and tenting effect of the simultaneously inserted dental implants seem to be sufficient for endo‐sinus bone gain. This is in line with histological findings from sites treated with membrane elevation without grafting that demonstrated bone tissue formation from the coagulum under the lifted membrane . Previous radiographic examinations identified OSFE procedure without grafting material as predictable treatment approach for posterior maxilla with limited residual bone height.…”
Section: Discussionsupporting
confidence: 83%
“…As an alternative to sinus lift with different grafting materials, graft‐free sinus lift was introduced in order to decrease invasiveness and increase cost‐effectiveness of the treatment . Histological studies have documented formation of new bone from void beneath the elevated Schneiderian membrane initially occupied by the coagulum as well as implant osseointegration . However, the mechanism behind the early bone formation under the lifted membrane is incompletely explained, and the role of the Schneiderian membrane in this process is controversial .…”
Section: Introductionmentioning
confidence: 99%
“…Bone formation by sinus membrane elevation has been proven in several studies (Lundgren et al, 2004(Lundgren et al, , 2008Palma et al, 2006;Cricchio et al, 2011aCricchio et al, , 2011bCricchio et al, , 2014Jungner et al, 2014).…”
Section: Resultsmentioning
confidence: 97%
“…And through the last decade many studies proofed that the Schneiderian membrane has the potential for bone formation even in the absence of any graft material in the sinus cavity due to the presence of osteoprogenitor cells . Conversely, other studies have shown that bone formation following sinus membrane elevation proceeds from the sinus floor along with the implants apices toward the elevated space …”
Section: Discussionmentioning
confidence: 99%